Correlative Factors of Severity of Air Bubbles in the Large Intestine during Colonoscopy - Yoshikawa, Takaaki; Yamauchi, Atsushi; Itami, Kumi; Odo, Shinichiro; Soma, Yoshihiro; Tanaka, Kosuke; Negoro, Kazuki; Mori, Yuki; Osawa, Kazuki; Itou, Ryou; Kawai, Yuya; Nakagami, Sota; Azuma, Shunjiro; Morita, Toshihiro; Hirohashi, Kenshiro; Kuriyama, Katsutoshi; Takahashi, Ken; Kou, Tadayuki; Katayama, Toshiro; Yazumi, Shujiro (Journal of Digestive Endoscopy, 2024)
Objectives The condition of air bubbles in the large intestine is an influential factor for good quality of colonoscopy. However, the correlative factors of severity of air bubbles during colonoscopy in the large intestine are not established. Therefore, this study aimed to elucidate the correlative factors influencing the severity of air bubbles in the large intestine.Materials and Methods A total of 314 examinees who underwent colonoscopy between August and September 2022 were enrolled (median age [range], 65 [18–88] years). Air bubbles were scored using the Colon Endoscopic Bubble Scale (CEBuS) and the clinical factors associated with the CEBuS scores, especially in the ileocecum, were analyzed.Results In this study, 39.8% (125/314) of examinees harbored severe air bubbles in the ileocecum. Multiple linear regression analysis revealed that the CEBuS scores in the ileocecum were positively associated with the interval time from completion of bowel preparation to intubation of the cecum (p = 0.0016) and a history of cholecystectomy (p = 0.0198). Logistic regression analysis between no, mild, and moderate air bubbles group (n = 189) and severe air bubbles group (n = 125) also showed that severity was positively associated with the interval time from completion of bowel preparation to intubation of the cecum (p = 0.0332) and a history of cholecystectomy (p = 0.0095).Conclusion Interval time and history of cholecystectomy were associated with severity of air bubbles in the large intestine after bowel preparation.
Keywords: colon; colonoscopy; colorectal polyp; endoscopy